2018
DOI: 10.1021/acs.est.8b04761
|View full text |Cite
|
Sign up to set email alerts
|

Priority Addressment Protocol: Understanding the Ability and Potential of Sanitation Systems to Address Priorities

Abstract: Sanitation acceptance is unlikely if user priorities are not addressed. However, sanitation systems 13 are commonly implemented, especially in resource-limited communities, without incorporating 14 local context. Understanding sanitation systems' abilities to address different priorities will further 15 inform technology selection processes. Therefore, a protocol was created to identify priorities and measure how well sanitation systems address them, based upon their importance to a community. This protocol wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 49 publications
0
33
0
Order By: Relevance
“…The sanitation system is an appropriate technology that therefore addresses a majority of the community's (most important) sanitation priorities; quantified using the priority addressment protocol (Davis et al, 2019). Black, 1998;Davis et al, 2019;Hacker and Kaminsky, 2017;Murphy et al, 2009;Palaniappan et al, 2008;Seymour, 2014; Case Knowledge…”
Section: Addressed Sanitation Prioritiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The sanitation system is an appropriate technology that therefore addresses a majority of the community's (most important) sanitation priorities; quantified using the priority addressment protocol (Davis et al, 2019). Black, 1998;Davis et al, 2019;Hacker and Kaminsky, 2017;Murphy et al, 2009;Palaniappan et al, 2008;Seymour, 2014; Case Knowledge…”
Section: Addressed Sanitation Prioritiesmentioning
confidence: 99%
“…The remaining two of the nine causal conditions were calibrated directly (i.e., 211 set membership is defined by continuously normalizing raw quantitative data within anchor points 212 (0, 0.5, 1) (Ragin, 2008)). For Addressed Sanitation Priorities, raw data for each case was a 213 quantitative priority addressment score, which reflects the extent to which priorities were 214 addressed based on importance (i.e., how appropriate the technology was to the local context) 215 (Davis et al, 2019) (SI Figure S1). For Sufficient O&M Funds, raw data for each case was the 216 amount of available funds as a percentage of monthly O&M costs (SI Figure S2).…”
Section: Technical Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…While applying this framework may produce rich insights into a particular context, the approach overall may be difficult to replicate due to resource needs that include external, highly skilled WASH professionals. Although we did not conduct a direct assessment of the replicability or scalability of each approach, we likely would have been hindered in doing so, since few studies, with some noted exceptions [37,70,71], reported on the resources that are required to implement the proposed approach. In order to better evaluate the practicality of these approaches, more reporting is needed on the resources required for studies which are applied across multiple contexts.…”
Section: Reporting On Resources and Replicabilitymentioning
confidence: 99%